Case Report: Hybrid low-grade fibromyxoid sarcoma and sclerosing epithelioid fibrosarcoma of the retroperitoneum - Burkitbayev, Zhandos; Zhaksylyk, Aruzhan; Ussipbekov, Baiduisen; Uskenbayev, Talgat; Kerimkulov, Altay; Sarina, Тomiris; Gogolev, Artem; Bolsinbekova, Saltanat; Sipenova, Aigerim (Frontiers in Oncology, 2026)
Retroperitoneal Sarcomas are rare malignancies that comprise 1%–2% of all malignant tumors. Among them, Low-Grade Fibromyxoid Sarcoma (LGFMS) and Sclerosing Epithelioid Fibrosarcoma (SEF) are ultra-rare sarcomas, especially in retroperitoneum. Hybrid LGFMS/SEF is even rarer, with limited cases reported in literature. We present the case of a 63-years old male with complaints on left hypochondrial discomfort, weight loss, and generalized weakness. Imaging revealed a large retroperitoneal mass with suspicion of local invasion. The patient underwent en-bloc surgical resection, including distal pancreatectomy, splenectomy, and left adrenalectomy. Histopathological examination confirmed a hybrid LGFMS/SEF with characteristic biphasic morphology. Hybrid LGFMS/SEF tumors exhibit features of both LGFMS and SEF sarcoma subtypes. Complete surgical resection remains the primary treatment strategy for localized disease. Because of the rarity of the disease, long-term surveillance is recommended. For advanced diseases, there are limited efficient available treatments necessitating the research of targeted therapies.